2020
DOI: 10.1017/epi.2020.49
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Self-Trust: It's Personal

Abstract: What is epistemic self-trust? There is a tension in the way in which prominent accounts answer this question. Many construe epistemic trust in oneself as no more than reliance on our sub-personal cognitive faculties. Yet many accounts – often the same ones – construe epistemic trust in others as a normatively laden attitude directed at persons whom we expect to care about our epistemic needs. Is epistemic self-trust really so different from epistemic trust in others? I argue that it is not. We certainly do rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Dormandy (2020) focuses on epistemic self‐trust and criticizes traditional accounts of epistemic self‐trust because they limit such self‐trust to reliance on one's capacities 2 . Instead, she suggests, epistemic self‐trust works more like interpersonal trust, it consists in trusting oneself, not just one's intellectual capacities.…”
Section: Three Framework For Evaluating Individual Intellectual Self‐...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dormandy (2020) focuses on epistemic self‐trust and criticizes traditional accounts of epistemic self‐trust because they limit such self‐trust to reliance on one's capacities 2 . Instead, she suggests, epistemic self‐trust works more like interpersonal trust, it consists in trusting oneself, not just one's intellectual capacities.…”
Section: Three Framework For Evaluating Individual Intellectual Self‐...mentioning
confidence: 99%
“…Instead, she suggests, epistemic self‐trust works more like interpersonal trust, it consists in trusting oneself, not just one's intellectual capacities. Her contribution is relevant to this discussion of valuable (and pernicious) intellectual self‐trust because her alternative conception of self‐trust enables her to argue that epistemic self‐trust is a healthy relationship with oneself (Dormandy, 2020, p. 12). The value of a healthy relationship with oneself is not captured by the epistemically consequentialist or virtue‐theoretic framework.…”
Section: Three Framework For Evaluating Individual Intellectual Self‐...mentioning
confidence: 99%
See 1 more Smart Citation
“…To explore that relation between intellectual self-trust and social exclusion it will be helpful to first say a little more about the nature of intellectual self-trust. As the nature of intellectual self-trust has been and is still the object of lively philosophical discussion and because accounts of the concept differ in detail (Dormandy 2020;El Kassar 2020Fricker 2016;Jones 2012;Tanesini 2020;Zagzebski 2012), I will not try to defend any substantial account. Instead I will focus on a minimal conception of intellectual self-trust as an attitude a person takes towards her own capacities to form beliefs, to give reasons for beliefs, and to reach an understanding of the world.…”
Section: Intellectual Self-trust: Individual Attitudes and Intersubje...mentioning
confidence: 99%
“…(Foley 2001)) and thus, what I take to be the first condition of intellectual self-trust. Taking into account questions about the aptness of intellectual self-trust in various social contexts and social mechanisms that undermine epistemic self trust, more recent accounts have shown that self-trust, just like interpersonal trust, involves more than mere reliance, (for example see Dormandy 2020).…”
Section: Intellectual Self-trust: Individual Attitudes and Intersubje...mentioning
confidence: 99%